Antibacterial ability of arabica (Coffea arabica) and robusta (Coffea canephora) coffee extract on Lactobacillus acidophilus - Willy Wijaya; Rini Devijanti Ridwan; Hendrik Setia Budi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Dental caries is the most commonly dental health problem found in Indonesia. Lactobacillus acidophilus (L. acidophilus) is bacteria playing a role in the development and continuation of caries. Some researches in Dentistry Faculty show that many plants are efficacious for oral health. One of them is coffee bean. Coffee bean containing caffeine, phenolic, trigonelline, and chlorogenic acid is reported to have antimicrobial activity. Purpose: This research aimed to determine the differences in the inhibition of Arabica and Robusta coffee extract to L. acidophilus. Method: This research was an laboratory experimental research. The method used was well diffusion method using seven samples for each treatment group. BHI-A and inoculated L.acidophilus bacteria was poured into each petri dish, and then 8 pitted holes were made with a diameter of 5mm and a depth of 3mm using a ring. Next, Arabica or Robusta coffee extracts at a concentration of 100%, 75%, 50%, 12.5%, 6.25%, and 3.125% were put into each of the pitted hole until it was full, and a negative control was also prepared. They then were put in an incubator at a temperature of 37 °C for 24 hours. Afterwards, measurements and observations were conducted on inhibition zone area. Result: Robusta coffee extract at the concentrations of 100% and 75% had greater inhibitory than Arabica coffee extract (p<0.05). Meanwhile, Arabica and Robusta coffee extracts at the concentrations of 50% and 25% had no significant inhibitory difference (p>0.05). Conclusion: In conclusion, Robusta and Arabica coffee extracts have inhibitory effects on L.acidophilus. Robusta coffee bean extract, nevertheless, has better inhibitory effects than Arabica coffee bean extract.